Efficacy of inhaled nitric oxide in preterm infants ≤ 34 weeks: a systematic review and meta—analysis of randomized controlled trials - Feng, Zhoushan; Wu, Xiaohong; Xu, Xiaona; Cui, Qiliang; Wu, Fan (Frontiers in Pharmacology, 2024)
Background: The effect of inhaled nitric oxide (iNO) in neonates >34 weeks on improving respiration is well documented. However, the efficacy of iNO in preterm infants ≤34 weeks remains controversial. Objectives: The main purpose of this review is to assess the effectiveness and safety of iNO treatment in preterm infants ≤34 weeks. Search methods: We systematically searched PubMed, Embase and Cochrane Libraries from their inception to 1 June 2023. We also reviewed the reference lists of retrieved studies. Selection criteria: Our study involved randomized controlled trials on preterm infants ≤34 weeks, especially those receiving iNO treatment, and mainly assessed outcomes such as bronchopulmonary dysplasia (BPD) and mortality. Two authors independently reviewed these trials, extracted data, and evaluated study biases. Disagreements were resolved by consensus. We used the GRADE method to assess evidence quality. Results: Our research included a total of 17 studies involving 4,080 neonates and 7 follow-up studies. The synthesis of results showed that in neonates, iNO treatment reduced the incidence of BPD (RR: 0.92; 95% CI: 0.86–0.98). It also decreased the composite outcome of death or BPD (RR: 0.94; 95% CI: 0.90–0.98), without increasing the risk of short-term (such as intraventricular hemorrhage, periventricular leukomalacia) and long-term neurological outcomes (including Bayley mental developmental index <70, cerebral palsy and neurodevelopmental impairment). Furthermore, iNO did not significantly affect other neonatal complications like sepsis, pulmonary hemorrhage, necrotizing enterocolitis, and symptomatic patent ductus arteriosus. Subgroup analysis revealed that iNO significantly reduced BPD incidence in neonates at 36 weeks under specific intervention conditions, including age less than 3 days, birth weight over 1,000 g, iNO dose of 10 ppm or higher, or treatment duration exceeding 7 days (p < 0.05). Conclusion: Inhaled NO reduced the incidence of BPD in neonates at 36 weeks of gestation, and the effect of the treatment depended on neonatal age, birth weight, duration and dose of iNO. Therefore, iNO can be considered a promising treatment for the potential prevention of BPD in premature infants. More data, however, would be needed to support nitric oxide registration in this specific patient population, to minimize its off-label use.